2009
DOI: 10.1115/1.3075874
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Selective Pulsed Laser Micropolishing on Microfabricated Nickel Samples Using Spatial Frequency Analysis

Abstract: The precision of parts created by microfabrication processes is limited by surface roughness. Therefore, as a means of improving surface roughness, pulsed laser micropolishing on nickel was examined numerically and experimentally. A one-dimensional finite element method model was used to estimate the melt depth and duration for single 50–300 ns laser pulses. The critical frequency was introduced to predict the effectiveness of polishing in the spatial frequency domain. A 1064 nm Nd:YAG laser with 300 ns pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Perry et al [1][2][3] have shown that knowledge of the maximum melt duration, t m-max , can be used to determine the minimum critical frequency, f cr , above which there should be a significant reduction in amplitude of the spatial frequency content of a surface and its asperities. The critical frequency is…”
Section: A Fluid Flow Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Perry et al [1][2][3] have shown that knowledge of the maximum melt duration, t m-max , can be used to determine the minimum critical frequency, f cr , above which there should be a significant reduction in amplitude of the spatial frequency content of a surface and its asperities. The critical frequency is…”
Section: A Fluid Flow Modelmentioning
confidence: 99%
“…Perry et al [1][2][3] have demonstrated that pulsed laser micro-polishing (PLμP) with pulse durations of 300-650 ns and a spot size of 60 µm is a method by which the surface roughness of microfabricated and micro milled parts can be effectively reduced. Improved surface finish and smoothness can be achieved on select areas of different metallic surfaces, produced by meso/micro-manufacturing processes, which is difficult via other methods (like mechanical polishing, electropolishing and chemical mechanical polishing) as the feature sizes are approaching the same magnitude as the surface roughness [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 is a schematic representation of the fundamental parts of the process, where a defocused beam is used to melt surface asperities in order to reach smoother topography. Once the material is melted, the attenuation of the asperities is given by several mechanisms such as capillary and gravitational forces, and recoil pressure [Perry, 2009] The process result depends mainly on three factors: the surface material, its initial topography and the energy density of the laser beam. The combination of these factors fixes the amount of melted material.…”
Section: Laser Polishing Fundamentals and Experimental Proceduresmentioning
confidence: 99%